Creative Thinking Curriculum Infusion for Students of Teachers’ Education Program - Mingchang Wu; Ibnu Siswanto; Wardan Suyanto; Yoga Guntur Sampurno; Weijen Tan (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
Creative thinking is consistently approved as a crucial competency for people to productively learn and succeed in this globalization and competition era. This article discusses the definition, major factors, and processes of creative thinking, and analyzes its improvement strategies. Furthermore, a curriculum infusion was proposed as an effective strategy to improve individual’s creative thinking in the universities, especially for teachers’ education program. The process of creative thinking curriculum infusion’s development consists of the following steps: (1) development of the creative thinking curriculum objectives, contents, and teaching strategies (2) selection of the existing courses to integrate creative thinking contents, and (3) implementation of creative thinking curriculum infusion model. This article finally suggests universities which provide teachers’ education program to extensively (1) integrate creative thinking contents into regular courses offered in the universities, (2) implement various creative thinking improvement strategies to deliver creative thinking contents, and (3) utilize a creative thinking self-assessment scale to measure students’ creative thinking. Moreover, a creative thinking curriculum infusion model as the recommended methods to improve learners’ creative thinking should be implemented to attain its empirical validation.